Effect of Mineral Nitrogen, Phosphorus, and Potassium Fertilizers on the Productivity of Faba Bean (Vicia faba L.) in Acidic Soils of Wolaita Zone, Southern Ethiopia - Bekalu Abebe Tsige; Nigussie Dechassa; Tamado Tana; Fanuel Laekemariam; Yibekal Alemayehu (International Journal of Agronomy)
Poor soil fertility is among the major factors that limit faba bean production in Wolaita Zone in southern Ethiopia. Therefore, a field experiment was conducted in the Kokate Marachare subdistrict of Sodo Zuria District of the zone during the 2019 and 2020 cropping seasons to determine the response of faba bean to different rates of nitrogen (N), phosphorus (P), and potassium (K) fertilizers under lime-treated soil conditions by using Tumsa faba bean variety. The treatments consisted of three rates of nitrogen fertilizer (0, 23, and 46 kg N ha−1), three rates of phosphorus fertilizer (0, 46, and 92 kg P2O5 ha−1), and three rates of potassium fertilizer (0, 30, and 60 kg K2O ha−1) that were laid out as RCBD and replicated three times per treatment. The results indicated that the N, P, and K fertilizer combination at 23:92:60 kg ha−1 increased plant height, the number of branches per plant, and stem girth by 18%, 62.6%, and 55.6%, respectively, compared with the control treatment. A significantly high aboveground dry biomass (11.8 t ha−1), number of pods per plant (17 pods), number of seeds per pod (4 pods), stover yield (6.83 t ha−1), and hundred seed weight (88 g) were obtained from the N, P, and K fertilizer combination at 23:92:60 kg ha–1. The highest grain yield (4.97 t ha−1) was obtained from the N, P, and K combination at 23:92:60 kg ha−1, which was 360% higher than the yield obtained from the control treatment. Moreover, the highest mean net benefit (USD 4,109.33 ha−1) with an acceptable marginal rate of return of 1,340% was obtained from the N, P, and K fertilizer combination at 23 kg N, 92 kg P2O5, and 60 kg K2O ha–1, respectively. Thus, these rates are suggested for faba bean production in the acidic soils of the Wolaita Zone.